Анализа на состојбата на лицата со интелектуална попреченост и комбинирани пречки во Република Македонија - Станојковска Трајковска, Наташа; Георгиевска, Софија; Каровска Ристовска, Александра; Каровска Андоновска, Билјана; Рашиќ Цаневска, Оливера (Helsinki Committee for Human Rights of the Republic of Macedonia, 2017)
The Helsinki Committee for Human Rights of the Republic of Macedonia within the project “Civil society support to social cohesion and diversity policy making” funded by the British Embassy in Macedonia, has prepared the Analysis of the situation of people with intellectual disability and combined disabilities in the Republic of Macedonia The analysis contains the research findings for the needs for changes of persons with intellectual disability and combined disabilities in several areas: social protection, education, health care, employment and quality of life.The analysis gives conclusions from the identified situations in each of the areas and recommendations for in law and by-laws changes in response to the identified conditions, in order to improve the situation of persons with intellectual disability and combined disabilities and their full integration in the society.
Analysis of the situation of people with intellectual disability and combined disabilities in the Republic of Macedonia
Keywords: persons with intellectual disability and combined disabilities in several areas, social protection, education, health care, employment and quality of life